2016
DOI: 10.1007/s13202-016-0276-0
|View full text |Cite
|
Sign up to set email alerts
|

Wax precipitation in multicomponent hydrocarbon system

Abstract: The objective of this research is to estimate individual effect of various external parameters such as pressure, cooling rate, watercut and addition of mechanical impurities on change in wax appearance temperature (WAT) in oil. In this paper, complex multicomponent system like oil is replaced to simplified model solution, presented by wax in kerosene solution. Research methods in the study were visual method at high-pressure/hightemperature conditions and rheological method under ambient pressure. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The crystal growth process then begins after the nuclei has stabilized as further molecules attach in a plate-like or lamellar structure. In general, the precipitation of wax can cause an increment in crude oil viscosity, although the adhesion of wax to the pipe wall does not occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal growth process then begins after the nuclei has stabilized as further molecules attach in a plate-like or lamellar structure. In general, the precipitation of wax can cause an increment in crude oil viscosity, although the adhesion of wax to the pipe wall does not occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread introduction of waterflooding at the initial stages of development, without taking into account the nature of wettability, led to the fact that in fields where the reservoir was predominantly hydrophobic, the pressure maintenance systems slightly affected oil recovery and led to sharp water cut due to uneven contraction of the oil-bearing contour during development, for example [22]. Also, studies [23][24][25] have shown that for low-permeability polymictic reservoirs it is more advantageous for the character of wettability to be initially hydrophilic. And in this case, the process of displacing oil from a porous medium is as close as possible to a piston.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This implies that the increase in wax concentration in solution leads to an increase in WAT. Struchkov and Rogachev (2017) studied the effect of pressure, cooling rate, water cut and addition of mechanical impurities on change in wax appearance temperature (WAT) in oil. Results show that WAT grows with an increase in the concentration of wax in solution, increase in pressure, water cut, shear rate, the addition of mechanical impurities and decrease in gap size of the measuring system.…”
Section: Wax Prevention By Temperature Controlmentioning
confidence: 99%